2016
DOI: 10.1007/s12369-016-0356-9
|View full text |Cite
|
Sign up to set email alerts
|

A Motivational Approach to Support Healthy Habits in Long-term Child–Robot Interaction

Abstract: We examine the use of role-switching as an intrinsic motivational mechanism to increase engagement in long-term child-robot interaction. The present study describes a learning framework where children between 9 and 11-years-old interact with a robot to improve their knowledge and habits with regards to healthy life-styles. Experiments were carried out in Italy where 41 children were divided in three groups interacting with: (i ) a robot with a role-switching mechanism, (ii ) a robot without a role-switching me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Children trusted humans more than robots in some contexts, whereas in other situations their trust in robots was greater than, or did not differ from, their trust in humans [17,18,120,123]. Findings for engagement were inconsistent [112,120,149], but children enjoyed an interaction more when they interacted with a friend than when they interacted with a robot [122,123]. However, regardless of whether they interacted with a robot or with an adult, children felt equally comfortable and experienced similar levels of enjoyment [17,149].…”
Section: Differences In Children's Interaction With Humans Robots Amentioning
confidence: 97%
See 2 more Smart Citations
“…Children trusted humans more than robots in some contexts, whereas in other situations their trust in robots was greater than, or did not differ from, their trust in humans [17,18,120,123]. Findings for engagement were inconsistent [112,120,149], but children enjoyed an interaction more when they interacted with a friend than when they interacted with a robot [122,123]. However, regardless of whether they interacted with a robot or with an adult, children felt equally comfortable and experienced similar levels of enjoyment [17,149].…”
Section: Differences In Children's Interaction With Humans Robots Amentioning
confidence: 97%
“…Although strategic and emotional interaction and cognitive states seemed to be associated [3, 57,59,81], no clear patterns were detected. However, memory-based interaction seemed to foster anthropomorphism [86,112]. Unless children's companionship expectations of a robot were violated [85], social presence remained constant over time across interaction styles [3, 82,127].…”
Section: Cognitive Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, children showed intentional (Guneysu & Arnrich, 2017;Hashimoto, Kato, & Kobayashi, 2011;Pulido et al, 2017; Saint-Aimé, Grandgeorge, Le Pévédic, & Duhaut, 2011; Saint-Aimé, Le Pévédic, & Duhaut, 2011) and behavioral acceptance (Wiles et al, 2016) of all social robots. Moreover, children showed the same degree of intentional acceptance towards a robot as to a human (Serholt, Basedow, Barendregt, & Obaid, 2014), an interactive video (Ros et al, 2016), and a tablet (Tozadore, Pinto, Ranieri, Batista, & Romero, 2017). For the tablet, this was also true for behavioral acceptance .…”
Section: Resultsmentioning
confidence: 63%
“…Children had a higher intentional acceptance of certain robot functions (e.g., providing education) compared to others (e.g., companionship) (Al-Taee et al, 2016), but their intentional acceptance was equal across different robot roles (i.e., friend vs. machine) (Westlund, Martinez, Archie, Das, & Breazeal, 2016). A third study (Ros et al, 2016) found no effect of role-switching on intentional robot acceptance. Finally, one study analyzed the effect of conversational violation (i.e., the robot bringing up information it could not possibly have) but did not find an effect on intentional acceptance (Leite & Lehman, 2016).…”
Section: The Effect Of Interaction Characteristics On Acceptancementioning
confidence: 99%